Exploring Secondary-school EFL Teachers’ Perception and Practices of Formative Assessment - Sulastini, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
Formative assessment is critical to effective classroom instruction and is widely acknowledged as a positive ‘facilitator’ of student learning and its careful implementation has powerful, positive effects on learning. This implies requirements for teachers to have an appropriate level of language assessment literacy or LAL since the effectiveness of teachers’ practices is much influenced by their perceptions or beliefs and related experiences. This study aims at obtaining better insights into English Foreign Language (EFL) teachers’ perceptions and practices of formative assessment. For this purpose, ninety-two EFL teachers of General and Vocational Secondary Schools in Jakarta and Bogor areas were involved as subjects of the study. The findings of the study reveal that teachers may not fully comprehend what FA is. This is reflected in the significant inconsistencies in their responses to the given questionnaires and interviews that suggest a misconception of FA. More rigorous study with better methodology is recommended as follow-up actions. In addition, the findings generate an urgent call for EFL teacher education programs to devise relevant professional development programs that can meet the actual needs of preset and inset program participants.